Anatomy and techniques in posterior urethroplasty - Gomez, Reynaldo G.; Scarberry, Kyle (Translational Andrology and Urology; Vol 7, No 4 (August 15, 2018): Translational Andrology and Urology (Male Genitourinary Reconstruction and Trauma), 2018)
Given its complex anatomy, injury to the posterior urethra may result in a number of reconstructive challenges. With the appropriate operative planning and experience, surgical repair can be very successful. This review discusses the applicable techniques for the perineal approach to posterior urethral stenosis, including bulbomembranous anastomosis for pelvic fracture urethral injury and repair of vesicourethral anastomotic stenosis (VUAS) following prostate surgery. The advanced techniques reviewed include an adaptation allowing a bulbar artery sparing approach to posterior urethroplasty and an intrasphincteric urethroplasty procedure which may allow continence preservation in patients with membranous urethral stenosis.